35.5k views
1 vote
6/a - 4/b = 1 and 9/a - 8/b = 1​

User Atrakeur
by
5.9k points

1 Answer

5 votes

Answer:

a = 3 ; b = 4

Explanation:

Eqn.1 =
(6)/(a) - (4)/(b) = 1

Eqn.2 =
(9)/(a) - (8)/(b) = 1

Both the eqns have RHS (Right Hand Side) equal. So,


(6)/(a) - (4)/(b) = (9)/(a) - (8)/(b)


= > (6b - 4a)/(ab) = (9b - 8a)/(ab)

Cancelling ab from both the denominators of both the sides,


= > 6b - 4a = 9b - 8a


= > 8a - 4a = 9b - 6b


= > 4a = 3b


= > a = (3b)/(4)

Putting the value of a in Eqn.1,


(6)/( (3b)/(4) ) - (4)/(b) = 1


= > (24)/(3b) - (4)/(b) = 1


= > (8)/(b) - (4)/(b) = 1


= > (8 - 4)/(b) = 1


= > b = 4

Putting the value of b in the value of a


a = (3 * 4)/(4) = 3

User Steven Lu
by
5.9k points